Aether's Hero's Journey in Genshin Impact (2020) - Alifagus Amri, Hanata Dhefa (Universitas Negeri Surabaya, 2025)
This study explores the depiction of the Hero's Journey, as outlined by Christopher Vogler, in the popular game Genshin Impact (2020), focusing on protagonist Aether's journey through the Mondstadt region. Using the Hero's Journey framework, this research analyzes how each stage-from “Ordinary World” to “Return with the Elixir” is represent in the quest, cutscenes, and character interactions in the game. In addition, it also investigates the role of character archetypes such as “Hero” to “trickster” in the quests Mondstadt region of Genshin Impact (2020). The result analysis that Aether is clearly depicted within the classical narrative structure twelve stages of the hero's journey which are Ordinary World, The Call of Adventure, Refusal of the Call, Meeting With The Mentor, Crossing the Threshold, Tests, Allies, and Enemies, Approach to the Inmost Cave, The Ordeal, Reward, The Road Back, The Resurrection, Return with the Elixir